INTEGRATING ENTREPRENEURSHIP EDUCATION INTO MSME DEVELOPMENT: A STRATEGIC MODEL FOR ENHANCING HUMAN RESOURCE QUALITY AND VILLAGE ENTREPRENEURSHIP IN GORONTALO REGENCY - Hinelo, Raflin; Abdul, Irawati; Selvi, Selvi; Machmud, Rizan; Asnawi, Melan Angriani; Hasan, Yusrin S.; Win, Thinzar (UNIVERSITAS NEGERI SURABAYA, 2025)
The low quality of human resources, exacerbated by a lack of access to structured entrepreneurship education, is a critical barrier to the development of Micro, Small, and Medium Enterprises (MSMEs). Acknowledging education as a fundamental driver of change, this study aims to formulate a strategic model for MSME development by integrating educational approaches to improve the quality of human resources (HR) and foster village entrepreneurship areas in Gorontalo Regency. A descriptive explanatory research method was employed, utilizing the Analytical Hierarchy Process (AHP) for analysis. Data were collected through focus group discussions and structured questionnaires administered to a panel of 21 experts, including MSME practitioners, government officials, and educational experts. The AHP results indicate that expanding access to practical entrepreneurship education and training is a primary strategy, underpinning the top priority of market access (weight: 0.417). This is followed by the core factor of human resource quality (0.271), which is directly addressed through educational interventions. Technology and innovation (0.147), government affirmative policies (0.131), and infrastructure support (0.035) complete the hierarchy. Consequently, the key policy implications are deeply rooted in education. It is recommended that local governments collaborate with educational institutions and the private sector to develop curricula for ongoing community-based education and training programs.